PERENCANAAN BISNIS BRIKET TEMPURUNG KELAPA BERBASIS WIRAKOPERASI DI KABUPATEN BOGOR - Fitria Na’imatu Sa’diyah; Lukman Mohammad Baga (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2016)
Bogor is capable of producing 16 208 tons of coconuts a year, and a big amount of coconut shells. This kind of shells can be a very valuable business commodity when processed into briquette. However the majority of Indonesian coconut farmers have only a little number of coconuts trees, so that the shell production is low and the farmers find it difficult to enter the briquette industry. Therefore, the coconut farmers need to join in the business based on cooperative approach to enter briquette industry.The coconut farmers who become members of the cooperative will get the guidance to process coconut shells into charcoal .The charcoal produced by farmers is used as raw material of making briquette. The market target of briquette will be Japan and the product will be sold at Rp11 829 per kilogram. This business gives financial benefit to the cooperative as the NPV is Rp5.1 milliards, gross B/C is 1.18, and payback period is 2 years 8 months. Nonfinancially, this business gives social benefit to the farmers who are members of the cooperative, because the cooperative buys the farmers’ charcoal in a good price, i.e. higher than the market price. Besides, those farmers will also get share profit from the cooperative.